RESPONSE OF FOLIAR APPLIED UREA ON GROWTH, YIELD AND QUALITY OF WHEAT (TRITICUM AESTIVUM L.) AT DIFFERENT GROWTH STAGES - SHAKOOR, A; QAMAR, M; ABBAS, SH; VASEER, SG; WAQAR, S; RASHID, K; IQBAL, H; KHALIL, MU; USMAN, M; HUSSAIN, I; et al. (Biological and Clinical Sciences Research Journal, 2024)
The cost of fertilizer manufacturing and the current energy crisis have increased, affecting the market supply. The situation gets acute when the availability of nitrogen fertilizer, particularly urea, is decreased during the wheat sowing season. As documented in the literature, when applied to plants through foliar, Urea fertilizer reduces the yellowing of lower leaves in wheat. The current research trial was designed to address these issues and reduce production losses caused by urea non-availability in wheat through foliar treatment at various growth stages. A field study was conducted in 2023-24 at the Wheat Program, National Agricultural Research Centre, Islamabad. The experiment consisted of two variables: a) different crop growth stages in the main plot (tilling, booting, and heading) and b) foliar urea application in subplots (control, 2%, 4%, 6%, 8%, and 10%). Yield components, grain yield data, nitrogen content in grain, and absorption were determined. The findings showed that foliar urea application significantly increased yield components and grain yield (grains per spike, productive tillers, 1000-grain weight, and grain yield), spike growth (spike length, spikelet per spike), biomass accumulation (biological yield, harvest index, and plant height) and quality attributes (nitrogen contents and grain crude protein). When applied at the heading stage, a foliar spray of 4 and 6% urea solution was the most effective at improving quantitative and qualitative traits. Applying 4% urea foliar spray is the most effective solution that increases grain yield by 30 per cent. Further increases in urea spray doses were shown to be inefficient due to its toxicity, which reduced grain yield.